Politik Popularitas Menurut Etika Kristen - dwi pramonojai, gilrandi aristya (Pusat Studi Pentakosta Indonesia, 2023)
Popularity politics cannot be separated from a democratic political system. Technological advances provide very wide space for political popularity. As a result, Christians often experience difficulties in responding to the political dynamics that occur. This study uses a literature review method with a descriptive qualitative approach. As a result, populist politics is incompatible with Christian ethics if it is not based on integrity. Christian ethics places truth and justice as the basis of ethics, which can result in someone becoming unpopular.Keywords: politics, integrity, ethicsPolitik popularitas tidak dapat dipisahkan dari system politik demokrasi. Kemajuan teknologi memberi ruang yang sangat luas bagi politik popularitas. Akibatnya orang Kristen sering mangalami kebingungan dalam meresponi dinamika politik yang terjadi. Studi ini menggunakan menggunakan metode kajian pustaka dengan pendekatan kualitatif dekriptif. Hasilnya politik popularitas tidak sesuai dengan etika Kristen jika tidak didasari dengan integritas. Etika Kristen menempatkan kebenaran dan keadilan sebagai etika dasar, yang dapat berdampak seseorang menjadi tidak populer.Kata Kunci : politik popularitas, integritas, etika